Identification and Profiling of Active Compounds from Golden Apple Snail’s Egg Pigments - Asadatun Abdullah; N. Nurjanah; Muhammad Reyhan (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Golden apple snail (Pomacea canaliculata) has been known as rice corps pest due to high adaptability and reproductive power. Utilization of Pomacea canaliculata’s eggs as raw materials in the food and health industry is one of the efforts to eradicate the pest snail. This study was aimed to identify the active compounds contained in the extract pigments of Pomacea canaliculata’s eggs. The methods of this study were extraction of pigments using acetone and methanol, analyzing the active compound (secondary metabolite) qualitatively, TLC to determine pigment components and LC-MS/MS to identify active compounds semi quantitatively. The results showed that active compounds in the methanol extract contain 11 carotenoid pigments of xanthophyl group, two carotenoid pigments of carotene group, and 2 active compounds in nonpigmented form, whereas the acetone extract contain 11 pigmentcarotenoids of xanthophyl group and 2 compounds active in non-pigment form.